Characteristics and Prognosis of Autoimmune Encephalitis in the East of China: A Multi-Center Study - Qiao, Shan; Wu, Huai-kuan; Liu, Ling-ling; Zhang, Ran-ran; Wang, Mei-ling; Han, Tao; Zhang, Shan-chao; Liu, Xue-wu (Frontiers in Neurology, 2021)
Background: The present study describes the clinical features, treatment, and long-term outcome of different subtypes of antineuronal surface antibody-associated limbic encephalitis in 76 Chinese patients to improve the clinical understanding, clinical diagnosis, and treatment of this disease. Methods: The clinical data of patients with limbic encephalitis associated with antineuronal surface antibodies diagnosed in multiple clinical centers were collected from May 2015 to May 2019. The recovery, hormone and antiepileptic drug maintenance time, and recurrent and residual symptoms of the patients were mainly evaluated. Results: The present study was conducted in 76 patients with limbic encephalitis associated with antineuronal surface antibodies, of which 58 patients had anti-LGI1 encephalitis, 16 patients had anti-gamma-aminobutyric-acid B (GABAB) receptor encephalitis, and 2 patients had anti-AMPA receptor encephalitis. The follow-up period ranged from 6 to 49 months. The clinical manifestations of different encephalitis subtypes have different characteristics. Serological tests, electroencephalography (EEG), and brain magnetic resonance imaging (MRI) exhibited varying degrees of abnormalities. Although most patients received first-line immunosuppressive therapy, differences were observed in the effectiveness of immunotherapy between different encephalitis subtypes. First-line immunotherapy was administered in 56 patients, and the modified Rankin score decreased by an average of 1.5 points after treatment. 51 patients were treated with antiepileptic drugs. Of the 46 patients followed up for 6 to 49 months, 7 exhibited recurrence. The prognosis of patients was generally good. In 16 patients with anti-GABAB receptor encephalitis, 13 received first-line immunotherapy. Of the 11 patients followed up for 7 to 34 months, 8 patients died and 1 experienced recurrence. Anti-AMPA receptor encephalitis was observed in 2 patients. The child with anti-AMPA type 1 receptor encephalitis responded well to immunotherapy, whereas the adult patients with anti-AMPA type 2 receptor encephalitis exhibited poor response after immunotherapy. Conclusions: The clinical manifestations, serological tests, EEG, and brain MRI exhibited varying degrees of abnormalities in different subtypes of antineuronal surface antibody encephalitis. Differences were observed in the effectiveness of immunotherapy between different subtypes of encephalitis. Immunosuppressive maintenance therapy is necessary in antineuronal surface antibody encephalitis. The present study provides a basis for the early recognition of different subtypes of encephalitis .